1985
DOI: 10.1037/0022-0167.32.4.551
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in career self-efficacy, consideration, and interests of eighth and ninth graders.

Abstract: Fifty-seven female and 51 male eighth-and ninth-grade college-bound students were assessed to determine relations between their self-efficacy, interest, and consideration of 10 traditionally male and female occupations. Sex differences were examined. Significant relations emerged suggesting that interest plays a major role in the consideration of both traditionally male and female occupations and that interest is a function of sex differences. Analysis of individual occupations revealed significant sex differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
5
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 12 publications
7
62
5
3
Order By: Relevance
“…(1992) examined the occupational and academic selfefficacy of a diverse sample of ninth-and tenth-grade rural students, who were very similar to the students in the Lauver & Jones (1991) study. Contrary to the Post-Kammer & Smith (1985) results, Noble et a1. found significant gender differences on occupational self-efficacy for more than half of the occupations sampled.…”
Section: Culture and Occupational Self-efficacycontrasting
confidence: 60%
See 2 more Smart Citations
“…(1992) examined the occupational and academic selfefficacy of a diverse sample of ninth-and tenth-grade rural students, who were very similar to the students in the Lauver & Jones (1991) study. Contrary to the Post-Kammer & Smith (1985) results, Noble et a1. found significant gender differences on occupational self-efficacy for more than half of the occupations sampled.…”
Section: Culture and Occupational Self-efficacycontrasting
confidence: 60%
“…In the Church et al (1992) study, the patterns of gender differences were found to exist whether the analysis was conducted at an aggregate level (across male-and female-dominated occupations) or at the level of specific occupations. Post-Kammer and Smith (1985) found some gender differences in the occupational self-efficacy expectations of eighth and ninth graders. With these younger students, however, gender differences were not as pervasive as they were with college students, and vocational interests emerged as a stronger predictor of the occupations students had considered than did occupational self-efficacy.…”
Section: Gender and Occupational Self-efficacymentioning
confidence: 91%
See 1 more Smart Citation
“…These scholars' work suggested that the differences in occupational status of women and men might reflect differences in career self-efficacy. Further support for Hackett and Betz's assertions were supported in the demonstration of gender differences in career self-efficacy (Betz & Hackett, 198 1 ;Betz & Hackett, 1986;Post-Kammer & Smith, 1985), with women demonstrating higher efficacy expectations than men for traditionally female occupations and men showing greater self-efficacy toward traditionally male occupations.…”
Section: Career Decision Self-efficacy (Cdse)mentioning
confidence: 86%
“…Girls reported a lower level of mathematics self-efficacy than did boys (Seegers, & Boekaerts, 1996). But the relationship between gender and mathematics self-efficacy is still unclear (Post-Kammer & Smith, 1985;Skaalvik & Rankin, 1994). Self-efficacy mediates the effect of gender and prior experience on math problem-solving performance (Pajares & Graham, 1999).…”
Section: Mathematics Self-efficacy and Mathematics Performancementioning
confidence: 99%